Prolonged hospitalization, primary refractory disease, performance status and age are prognostic factors for survival in patients with diffuse large B-cell lymphoma and transformed indolent lymphoma undergoing autologous stem cell transplantation. Issue 5 (4th May 2018) - Arboe, Bente; Halgren Olsen, Maja; Duun-Henriksen, Anne Katrine; Gørløv, Jette Sønderskov; Nielsen, Kristina Fruerlund; Thomsen, Rasmus Heje; Madsen, Charlotte; Nielsen, Søren Ramme; Dalton, Susanne Oksbjerg; Brown, Peter de Nully
Abstract: In patients with relapsed diffuse large B-cell lymphoma (DLBCL), high-dose chemotherapy followed by autologous stem cell transplantation (ASCT) is standard treatment. Here, we aim to identify factors associated with survival in patients undergoing ASCT. A total of 369 patients with relapsed DLBCL undergoing ASCT from 2000 to 2012 were identified in the Danish National Lymphoma Registry. Information on clinical and socioeconomic factors was obtained from medical records and national registries. Factors associated with survival were assessed using a Cox's proportional hazards model. Median overall survival was 6.8 years, median progression-free survival was 2.6 years, and treatment-related mortality at Day 100 was 6%. Factors associated with a significant adverse impact on survival were age, primary refractory disease, prolonged hospitalization during salvage treatment, and performance status >0 prior to conditioning therapy. Reconsideration of ASCT for those patients may be required in order to select the right patients for this toxic procedure.